The physiological mechanism for sensing nasal airflow: A literature review. Issue 10 (30th July 2014) - Sozansky, Jeanie; Houser, Steven M.
<x xml:space="preserve">Abstract</x> Background Nasal obstruction is a common otolaryngologic complaint, yet the mechanism of sensing airflow is not commonly understood. The objective of this work was to review current knowledge on the physiological mechanism for sensing nasal airflow. Methods Current literature pertaining to nasal sensation to airflow was retrieved using PubMed and Google Scholar searches. Results The primary physiological mechanism that produces the sensation of ample nasal airflow is activation of trigeminal cool thermoreceptors, specifically transient receptor potential melastatin family member 8 (TRPM8), by nasal mucosal cooling. The dynamic change in temperature is ultimately sensed. Nasal mucosal cooling is a result of conductive heat loss, driven by temperature gradient, and evaporative heat loss, driven by humidity gradient. The perception of ample nasal airflow is dependent on the overall nasal surface area stimulated by mucosal cooling, which is mainly governed by air flow patterns. Cool thermoreceptors in the nasal mucosa are connected to the respiratory centers and consequently can alter respiration patterns. Mechanoreceptors do not seem to play a role in sensing nasal airflow. Computational fluid dynamics (CFD) modeling could be a valuable objective tool in evaluating patients with nasal congestion. Conclusion Understanding the physiological mechanism of how the nose senses airflow can aid in diagnosing the cause behind patient symptoms, which allows physicians to provide better treatment options for patients. ©2014 ARSAAOA, LLC.